2016
DOI: 10.1093/ee/nvw136
|View full text |Cite
|
Sign up to set email alerts
|

Finding Prospective Mates by the Parasitoid WaspUrolepis rufipes(Hymenoptera: Pteromalidae)

Abstract: Cues from emergence sites may be predictive of mating opportunities if potential mates are slow to disperse after emergence, and particularly if emergence sites are clumped, as in the solitary parasitoid wasp Urolepis rufipes Ashmead. Males emerge before females, and the present study suggests that males may use emergence sites of conspecific males to locate mates. In choice experiments, virgin males spent more time on a male-emerged host (a host from which a male had recently emerged) than on a female-emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Furthermore, Ur males increase marking activity in the presence of females and when fed honey (Cooper and King, 2015). Virgin females prefer areas where multiple males have marked over areas where a single male has marked (Wittman et al, 2016). Taken together, these results suggest that Ur males use a substrate-borne sex pheromone in a similar manner as described for Nasonia males.…”
Section: Introductionmentioning
confidence: 52%
“…Furthermore, Ur males increase marking activity in the presence of females and when fed honey (Cooper and King, 2015). Virgin females prefer areas where multiple males have marked over areas where a single male has marked (Wittman et al, 2016). Taken together, these results suggest that Ur males use a substrate-borne sex pheromone in a similar manner as described for Nasonia males.…”
Section: Introductionmentioning
confidence: 52%
“…4 The infochemicals parasitoids exploit are plant volatiles [5][6][7][8] or herbivore-associated chemicals such as pheromones. [9][10][11][12] Many studies have identified infochemical components emitted from different host's herbivore stages (eggs, larvae/nymphs, pupae, adults) and host herbivore by-products (e.g., frass, honeydew, exuviae, mandibular gland secretions, defense secretions, etc.). [13][14][15][16] These host compounds play a key role that might guide the parasitoids locating decisions.…”
Section: Introductionmentioning
confidence: 99%
“…These include the use of trail sex pheromone deposited by females in Aphelinus asychis (Fauvergue et al, 1995), Aphytis melinus (Bernal and Luck, 2007), and Trichogramma brassicae (Pompanon et al, 1997). Urolepis rufipes use territorial markings (Cooper and King, 2015) and emergence sites of conspecific males (Wittman et al, 2016) to attract females. In some parasitoid wasps, mate-finding involves using chemical cues from the hosts themselves (Vinson, 1976).…”
Section: Introductionmentioning
confidence: 99%